Filosofi Pendidikan Berbasis Karakter dalam Pandangan Muhammadiyah: Kajian Pemikiran KH. Ahmad Hahlan - Azzahra, Rahma; Ghinanjar, M. Yusron; Azzahra, Nur Azizah; Abdillah, Muh. Asyraf (Masterpiece: Journal of Islamic Studies and Social Sciences, 2025)
Character education has become a major concern in addressing the moral and social crises of the modern era. Muhammadiyah, as one of the largest Islamic organizations in Indonesia, holds a strong commitment to building a character-based education system deeply integrated with Islamic values. This study aims to explore the educational philosophy of character formation according to KH. Ahmad Dahlan, the founder of Muhammadiyah, and its relevance to contemporary educational challenges. The method used is a literature review by analyzing primary and secondary sources including books, academic journals, and historical documents related to KH. Ahmad Dahlan's thoughts. The findings reveal that KH. Ahmad Dahlan developed a holistic and integrative educational concept that emphasizes not only cognitive development but also spiritual, moral, and social dimensions. He stressed the importance of integrating religious and general sciences, the moral example of teachers, the cultivation of akhlaqul karimah (noble character), and the practical application of values in students' lives. This concept is implemented through an integrated curriculum, extracurricular activities, value-based school environments, and the utilization of digital technology in strengthening character education. KH. Ahmad Dahlan’s ideas remain highly relevant in addressing today’s educational issues, such as identity crises, moral degradation, radicalism, gender inequality, and the need for 21st-century skills. His model of character education aims to form religious, intelligent, independent, and socially responsible individuals. With a progressive and contextual approach, his educational philosophy serves as a foundational pillar for developing an adaptive, solution-oriented, and future-focused Islamic education system.